2019
DOI: 10.1039/c9cc02380a
|View full text |Cite
|
Sign up to set email alerts
|

Ti cluster-alkylated hydrophobic MOFs for photocatalytic production of hydrogen peroxide in two-phase systems

Abstract: The photocatalytic activity of a cluster-alkylated MOF for H2O2 production far exceeded that of a linker-alkylated MOF in a benzyl alcohol/water two-phase system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 26 publications
0
42
0
1
Order By: Relevance
“…More recently,t his research group illustrated that the grafted alkyl chains in the MIL-125-R7 would block some of the pores,thereby leading to ad ecreased surface area and thus al ower photocatalytic activity of this system. [120] To address this problem, they employed octadecylphosphonic acid (OPA) for the alkylation of MIL-125-NH 2 ,w hich only enabled modification of the Ti 8 O 8 (OH) 4 moieties with open coordination sites.T he obtained OPA/MIL-125-NH 2 also was also hydrophobic and maintained approximately 83 %o ft he surface area of MIL-125-NH 2 .I nt he two-phase BA/water photocatalytic system, the maximum H 2 O 2 concentration obtained utilizing OPA/ MIL-125-NH 2 was about 3-times higher than that of MIL-125-R7 after irradiation with visible light for 3h.…”
Section: Coordination Polymersmentioning
confidence: 99%
“…More recently,t his research group illustrated that the grafted alkyl chains in the MIL-125-R7 would block some of the pores,thereby leading to ad ecreased surface area and thus al ower photocatalytic activity of this system. [120] To address this problem, they employed octadecylphosphonic acid (OPA) for the alkylation of MIL-125-NH 2 ,w hich only enabled modification of the Ti 8 O 8 (OH) 4 moieties with open coordination sites.T he obtained OPA/MIL-125-NH 2 also was also hydrophobic and maintained approximately 83 %o ft he surface area of MIL-125-NH 2 .I nt he two-phase BA/water photocatalytic system, the maximum H 2 O 2 concentration obtained utilizing OPA/ MIL-125-NH 2 was about 3-times higher than that of MIL-125-R7 after irradiation with visible light for 3h.…”
Section: Coordination Polymersmentioning
confidence: 99%
“…The use of a bi-phasic solvent system has the potential to lead to enhanced selectivity towards H 2 O 2 , through minimising contact time between H 2 O 2 , the catalyst and reactant gases, which in turn leads to a reduction in the subsequent H 2 O 2 degradation reactions and, thus, an increase in H 2 O 2 concentration. Indeed similar approaches have been recently been reported for the production of H 2 O 2 via photocatalytic processes [38][39][40] as well as in the biomass conversion literature, where bi-phasic solvent systems often lead to higher product yields than with mono-phasic aqueous systems due to the higher solubility of products in the organic phase. 41 Furthermore, the use of multi-phasic systems has been well established in processes that utilise homogeneous catalysts.…”
Section: Introductionmentioning
confidence: 59%
“…Due to the introduction of hydrophobicity on pore surface and the inductive effects of the N ‐alkyl groups, MIL‐125‐NHR showed improved stabilities and increased reaction rates and quantum yields in the photocatalytic reduction of carbon dioxide under blue light. Yamashita and coworkers recently reported that a photoactive MOF, MIL‐125‐NH 2 , could be hydrophobized by the alkylation of its linkers with different acid anhydrides or by the modification of its outermost surface with octadecylphosphonic acid (OPA) and that these hydrophobic phases exhibited high photocatalytic activities in the production of H 2 O 2 , which was carried out in a two‐phase system (benzylalcohol/water). Thanks to their hydrophobicity, the MOF catalysts stayed in the organic phase ( Figure ), and the highly acidic aqueous phase could be employed to facilitate H 2 O 2 production.…”
Section: Potential Applicationsmentioning
confidence: 99%